PROCESSING FUNCTION OF AGRICULTURAL LANDS IN RURAL COMMUNITY DYNAMICS - Hidayat, Wahyu; Siswanto, Prof. Dr. Budi; NGW, Prof. Dr. Bonaventura (IJRDO - Journal of Social Science and Humanities Research, 2018)
The objectives of this research are to (1) Describe and analyze the process of agricultural land function in the dynamics of rural communities (2) to describe and analyze the social impacts caused by the processing of agricultural land functions in the dynamics of rural communities. The problems studied are (1) how is the processing of agricultural land functions in the dynamics of rural communities ?; (2) what are the social impacts of agricultural land cultivation in the dynamics of rural communities?. The method used is qualitative research method. The analytical technique in this study refers to Grounded research by Straus and Corbin. Instrument used in this research is "human instrument", researcher own with technique of taking data: interview, observation, and documentation. Based on the results of this study can be concluded that (1) Tajinan people fully aware of the government’s policy program on the processing of agricultural land into shophouse. In the development of time and progress of time, then there is processing function. Their lands are sold to developers with a variety of current realistic arguments and views; (2) In the process of processing and marketing occurs a dynamics in society. The land lot owners always communicate with the local community, so that a harmonious social relationship is established. (3) The pattern of their association has also experienced a dominant change. People are generally happy because they have started to see and understand the prospects of life in the future. In addition, there are also impacts, both positive and negative.